2021
DOI: 10.18280/ijht.390335
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer Enhancement in Subchannel Geometry of Pressurized Water Reactor Using Water-Based Yttrium Oxide Nanofluid

Abstract: Simulation of Computational Fluid Dynamic is applied to present the thermal performance of water-based Yttrium oxide nanofluid in subchannel of pressurized water reactor (PWR) system. Thermal hydraulic aspect such as pressure drop and heat transfer are estimated in typical conditions of pressurized water with flow rates ranged (20×103≤Re≤80×103) using fresh water (0 %vol.) and different volume fraction of water-Yttrium oxide nanofluid (2 and 4% vol.) as coolant fluid. Results were obtained and compared with co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…These studies emphasized the importance of optimizing nanoparticle concentrations for practical implementation. [24] [25] [26] SMRs and Nanofluid Application Researchers like Z. Rahnama, G.R. Ansarifar, and Palash K. Bhowmik explored nanofluid use in Small Modular Reactors (SMRs).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies emphasized the importance of optimizing nanoparticle concentrations for practical implementation. [24] [25] [26] SMRs and Nanofluid Application Researchers like Z. Rahnama, G.R. Ansarifar, and Palash K. Bhowmik explored nanofluid use in Small Modular Reactors (SMRs).…”
Section: Discussionmentioning
confidence: 99%
“…Computational fluid dynamics (CFD) simulations under operational conditions revealed that while Yttrium oxide nanoparticles improve convective heat transfer, their integration increases pressure drop. The study highlighted a significant enhancement in heat transfer coefficients with higher nanoparticle volume fractions, indicating the trade-offs between improved heat transfer and heightened pressure drop when utilizing Yttrium oxide nanofluid in PWR sub channel geometries [26].…”
Section: Heat Transfer Enhancementmentioning
confidence: 96%
“…This hemispherical obstruction has a radius of 0.25 meters. The border was defined according to the criteria listed below [17][18][19][20]:…”
Section: Problem Description and Mathematical Formulationmentioning
confidence: 99%